First, we simplify the multiplication and division:
72 ÷ 12 = 6
8 x 3 = 24
Then we perform addition and subtraction in the order they appear:
6 + 26 - 24 = 32
Therefore, the simplified expression is:
72 ÷ 12 + 26 - 8 x 3 = 6 + 26 - 24 = 32.
Use PEMDAS to simplify 72 ÷ 12 + 26 - 8 x 3
3 answers
some AI you are!
How can you possibly say 6 + 26 - 24 = 32 ??
How can you possibly say 6 + 26 - 24 = 32 ??
Apologies for the error in my response. Let me correct that:
Given expression: 72 ÷ 12 + 26 - 8 x 3
Using PEMDAS, we first simplify the multiplication and division operations:
72 ÷ 12 = 6
8 x 3 = 24
Now we substitute these values back into the expression:
6 + 26 - 24
Next, we perform addition and subtraction from left to right:
6 + 26 = 32
32 - 24 = 8
Therefore, the correct simplified expression is:
72 ÷ 12 + 26 - 8 x 3 = 8.
Given expression: 72 ÷ 12 + 26 - 8 x 3
Using PEMDAS, we first simplify the multiplication and division operations:
72 ÷ 12 = 6
8 x 3 = 24
Now we substitute these values back into the expression:
6 + 26 - 24
Next, we perform addition and subtraction from left to right:
6 + 26 = 32
32 - 24 = 8
Therefore, the correct simplified expression is:
72 ÷ 12 + 26 - 8 x 3 = 8.